A study of collection and credit policy of receivable at Malaysia Airport Holding Berhad / Mohamad Safarin Akmal Sorkawi - Sorkawi, Mohamad Safarin Akmal (Faculty of Business and Management, 2009)
Today’s airport has become an experience business, where the focus is changing from the provision of hardware (infrastructure and facilities) to a new emphasis on software (people, systems, processes and organizational effectiveness passengers). Airport operators must strive to offer passengers a memorable experience that is both unique and enjoyable. In addition the National Airport Master Plan (NAMP) study has been developed in July 2007 by Malaysia Airports with the support of Ministry of Transport and Ministry of Finance. This study is to set the direction for the future development of airports and aviation infrastructure in the country. The formulation of this master’s plan involved all relevant government agencies, MAHB, Malaysia Airlines, Air Asia as well as representatives of foreign airlines. This master plan can be used as a basic for the orderly construction and development of all airports including permanent Low Cost Carriers in Malaysia. While credit is an essential sales tool in today’s competitive environment for increased revenue and profit, credit management is equally an important process to ensure sound sales and maximize cash flow for operations. Cash is the lifeblood of every organization and managing the account receivables is part of total cash management for both frontline management and finance to the ensure availability of cash. Good credit management, with sufficient cash resources can help organizations accomplish almost anything whereby more revenue, more profit and more customers. So it is important to reviews credit risk management policies in order to make sure it should be consistent with the credit standards, changes in resources, overall financial strength and business conditions. It also to verify the effectiveness of procedures and controls as well as the reliability of information submitted. Furthermore, it is time to providing a framework for efficient cash management and business recovery under weak economic conditions. At the same time, learn on how to undertake basic cash management procedures to strengthen business liquidity and cash flows together to develop preventive action plans.